A new species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Tocantins state, Brazil - Orlando, Thales Yann; Krolow, Tiago Kütter; Boldrini, Rafael (Zootaxa, 2019)
There are seven genera and eight species of mayflies recorded for Tocantins state, Brazil, but only three belonging to the family Leptophlebiidae. Based on male imagoes, Simothraulopsis primus sp. nov. is described from Tocantins state, Northern Brazil. The species is characterized by the male genitalia being short, lanceolate, with a straight spine and by the “U” shape between the penis lobes. Other distinguishing features are the brown thorax and yellowish brown abdomen.